A low-temperature tear-resistant silicone sealant and preparation method thereof
By using modified nano calcium carbonate and polylactic acid in low-temperature tear-resistant silicone sealant to form a network structure and adding dimethyl silicone oil, the problem of traditional sealant becoming hard and brittle in low-temperature environments is solved, and the low-temperature tear resistance and waterproofness of the sealant is significantly improved.
Patent Information
- Application Number
- CN202411285101.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Traditional low-temperature tear-resistant silicone sealants tend to harden and become brittle in low-temperature environments, and the tear strength is relatively low, resulting in tear and degumming problems after use.
Hydroxy-terminated polydimethylsiloxane is used to combine with modified nano-calcium carbonate, polylactic acid and other additives. The modified nano-calcium carbonate is modified by trehalose and polyvinyl alcohol to form a network structure to jointly strengthen the sealant, and dimethyl silicone oil is added to disperse the modified nano-calcium carbonate and polylactic acid to improve the low-temperature tear resistance of the sealant.
It significantly improves the tear resistance of sealant in low temperature environments, avoids tear and degumming problems, and maintains good waterproofness and UV oxidation resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sealants, and more particularly to a low-temperature tear-resistant organic silicon sealant and a preparation method thereof. Background Art
[0002] Silicone sealant is a paste made of polydimethylsiloxane as the main raw material, supplemented by cross-linking agents, fillers, plasticizers, coupling agents, and catalysts mixed under vacuum conditions. It solidifies into elastic silicone rubber by reacting with water in the air at room temperature.
[0003] Low temperature tear resistant silicone sealant is one of the fastest growing products in the silicone market. Commonly used is low temperature tear resistant silicone sealant represented by single component room temperature vulcanized silicone rubber (RTV). Its main features are excellent weather resistance and easy construction. Therefore, RTV is widely used in civil engineering, construction, electronics, vehicle transportation, aircraft and ships, machinery, chemical industry, light industry and other fields.
[0004] However, traditional low-temperature tear-resistant silicone sealants tend to become hard and brittle in low-temperature environments, especially below -50°C. The tear strength is significantly low, leading to tearing and degumming problems after use. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a low-temperature tear-resistant silicone sealant and a preparation method thereof.
[0006] In a first aspect, the present invention provides a low-temperature tear-resistant silicone sealant, comprising the following raw material components in parts by weight: 100 parts of hydroxyl-terminated polydimethylsiloxane, 60-80 parts of modified nano-calcium carbonate, 15-20 parts of polylactic acid, 10-15 parts of dimethyl silicone oil, 8-12 parts of a cross-linking agent, 3-5 parts of a coupling agent, and 1-2 parts of a catalyst;
[0007] The preparation method of the modified nano calcium carbonate comprises the following steps: adding trehalose to a saturated Ca(OH)2 slurry and stirring evenly, then introducing CO2 gas and the saturated Ca(OH)2 slurry for mixing and carbonization, when the pH value of the system is 9±0.2, heating to 80-85°C and then adding polyvinyl alcohol, after uniform dispersion, cooling and continuing to introduce CO2 gas for mixing, when the pH value of the system is 7.5±0.2, stopping introducing CO2 gas to obtain a modified CaCO3 slurry; and filtering, drying and pulverizing the modified CaCO3 slurry to obtain the modified nano calcium carbonate.
[0008] The organic silicon sealant of the present invention adopts hydroxyl-terminated polydimethylsiloxane and specific modified nano-calcium carbonate, polylactic acid and other additives to be compounded in strict accordance with the set amount. The modified nano-calcium carbonate has more side chain groups after being composite-modified by trehalose and polyvinyl alcohol. The groups can not only make the nano-calcium carbonate uniformly dispersed in the hydroxyl-terminated polydimethylsiloxane to participate in the cross-linking reaction, but also form a bond with the polylactic acid to form a network structure. The formed network structure can still remain intact under low temperature environment due to the presence of trehalose. Therefore, the nano-calcium carbonate and the polylactic acid can synergistically reinforce the organic silicon sealant under low temperature environment. Then, by utilizing the characteristics of low viscosity and good compatibility of dimethyl silicone oil, the added set amount of dimethyl silicone oil can be well dispersed in the gap of the network structure to prevent the modified nano-calcium carbonate and the polylactic acid from agglomerating. The organic silicon sealant prepared in this way has excellent low-temperature tear resistance.
[0009] The modified nano-calcium carbonate is prepared by first adding a set amount of trehalose to a saturated Ca(OH)2 slurry. Trehalose contains abundant hydroxyl groups in its molecular structure. These polar groups form hydrogen bonds with water molecules, thereby being able to bind a large amount of water to initially promote nucleation. The solution is then heated to 80-85°C to allow polyvinyl alcohol to dissolve quickly in the system. The hydroxyl groups in the molecular structure of polyvinyl alcohol are then used to further promote nucleation, thereby allowing calcium carbonate crystals to form stably and continuously, and the formed crystal structure is more fine and regular, so that the nano-calcium carbonate obtained can function better.
[0010] In addition, the side chain groups in the molecular structure of trehalose can also form hydrogen bonds with calcium carbonate, so that trehalose can be uniformly adsorbed on the surface of calcium carbonate, the polar groups of polyvinyl alcohol can prompt it to quickly disperse and attach to the surface of calcium carbonate after trehalose modification, and then utilize the compatibility and adhesion of polyvinyl alcohol with polymers to prompt calcium carbonate to be uniformly and stably dispersed in the sealant substrate, thereby effectively improving the cross-linking effect of the sealant substrate and calcium carbonate. In addition, by first adding trehalose, and then adding the modification step of polyvinyl alcohol, on the one hand, trehalose is smaller than the molecular structure of polysaccharides such as chitosan, and promotes high nucleation efficiency, and can continuously promote nucleation while adhering to the surface of calcium carbonate, on the other hand, the entanglement of the added molecular chain of polyvinyl alcohol and the cross-linking effect make the surface of calcium carbonate realize better coating and modification, promote dispersion, and therefore can obtain a modified calcium carbonate with smaller particle size and better dispersibility. Since the two modified raw materials of nano calcium carbonate do not contain metal ions such as Na+, the modified nano calcium carbonate obtained does not contain metal ions such as Na+, thereby effectively reducing the content of metal ions such as Na+ in the sealant to ensure its mechanical properties.
[0011] Preferably, the added amount of trehalose is 5-8% by weight of the saturated Ca(OH)2 slurry.
[0012] Preferably, the amount of polyvinyl alcohol added is 3-6% by weight of the saturated Ca(OH)2 slurry.
[0013] Preferably, the weight ratio of the trehalose to the polyvinyl alcohol is 3:2.
[0014] By using the above technical scheme, if the amount of trehalose and polyvinyl alcohol is too much, the modified nano-calcium carbonate obtained will have a certain water absorption due to the increase in polar groups, which will affect the waterproofness of the sealant to a certain extent; if the amount of trehalose and polyvinyl alcohol is too little, the modified nano-calcium carbonate obtained will be difficult to stably cross-link hydroxyl-terminated polydimethylsiloxane and polylactic acid. Therefore, in order to ensure the excellent effect of the present invention, it is necessary to further control the amount of trehalose and polyvinyl alcohol, and the above amount is further preferred.
[0015] Preferably, the weight ratio of the modified nano-calcium carbonate, the polylactic acid and the dimethyl silicone oil is 72:18:12.
[0016] Using the above technical scheme, modified nano-calcium carbonate, polylactic acid and dimethyl silicone oil are the key components for realizing the low-temperature tear resistance of the sealant of the present invention. After a large number of experiments and verifications, the change in the amount of the three in the present invention has a great influence on the performance of the silicone sealant. When they are configured in a weight ratio of 72:18:12, the obtained silicone sealant has more excellent low-temperature tear resistance, so it is further preferred.
[0017] Preferably, the hydroxyl-terminated polydimethylsiloxane is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 10000-50000 mPa·s at 25°C and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 500000-1000000 mPa·s at 25°C in a weight ratio of 75-80:25-20.
[0018] Preferably, the hydroxyl-terminated polydimethylsiloxane is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 20,000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 600,000 mPa·s at 25° C. in a weight ratio of 4:1.
[0019] By adopting the above technical scheme, the hydroxyl-terminated polydimethylsiloxane of the present invention is compounded with a low-viscosity type and a high-viscosity type in a specific ratio, wherein the low-viscosity type can be evenly and quickly dispersed with the modified nano-calcium carbonate and polylactic acid and complete preliminary cross-linking, while the high-viscosity type is interspersed in the low-viscosity type as a skeleton, and further cross-linking is completed by utilizing the fluidity of the low-viscosity type, so that the sealant obtained has higher low-temperature tear resistance.
[0020] Preferably, 10-15 parts of fumed silica are also included.
[0021] Preferably, the weight ratio of the fumed silica to the modified nano-calcium carbonate is 1:6.
[0022] By adopting the above technical scheme, a set amount of fumed silica is added to the silicone sealant of the present invention to cooperate with the modified nano-calcium carbonate, so that the cross-linking effect of the sealant can be further increased, and the obtained sealant has more excellent low-temperature tear resistance. In addition, silica has a large specific surface area and surface activity, and can absorb ultraviolet rays to a certain extent, and then cooperate with the trehalose in the modified nano-calcium carbonate to improve the anti-ultraviolet oxidation performance of the sealant.
[0023] In a second aspect, the present invention provides a method for preparing a low-temperature tear-resistant silicone sealant, comprising the following steps:
[0024] Divide a set amount of modified nano-calcium carbonate into two parts, take one part of the modified nano-calcium carbonate and first blend it with a set amount of hydroxyl-terminated polydimethylsiloxane and polylactic acid at a temperature of 160-170° C. and a vacuum degree of -0.06 to -0.09 MPa for 30 minutes, then take another part of the modified nano-calcium carbonate and add it and continue blending for 60-80 minutes, and obtain a base material after cooling;
[0025] The base material is mixed with a set amount of dimethyl silicone oil, a crosslinking agent, a coupling agent, and a catalyst, and stirred for reaction for 60-120 minutes under a vacuum degree of -0.08 to -0.09 MPa to obtain the low-temperature tear-resistant silicone sealant.
[0026] When preparing the organosilicon sealant, the modified nano-calcium carbonate is mixed with the hydroxyl-terminated polydimethylsiloxane in two times. Compared with adding at one time, the dispersing efficiency of the mixed method in the present invention is higher, and it is more helpful for the hydroxyl-terminated polydimethylsiloxane to achieve step-by-step cross-linking, thereby improving the cross-linking effect of the sealant and further improving the low-temperature tear resistance of the sealant.
[0027] In a third aspect, the present invention provides another method for preparing a low-temperature tear-resistant silicone sealant, comprising the following steps:
[0028] Divide a set amount of modified nano-calcium carbonate into two parts, take one part of the modified nano-calcium carbonate and first blend it with a set amount of hydroxyl-terminated polydimethylsiloxane and polylactic acid at a temperature of 160-170° C. and a vacuum degree of -0.06 to -0.09 MPa for 30 minutes, then take another part of the modified nano-calcium carbonate and fumed silica and add them and continue blending for 60-80 minutes, and obtain a base material after cooling;
[0029] The base material is mixed with a set amount of dimethyl silicone oil, a crosslinking agent, a coupling agent, and a catalyst, and stirred for reaction for 60-120 minutes under a vacuum degree of -0.08 to -0.09 MPa to obtain the low-temperature tear-resistant silicone sealant.
[0030] In the present invention, the fumed silica is added together with the modified nano-calcium carbonate for the second time. At this time, the hydroxyl-terminated polydimethylsiloxane has completed preliminary cross-linking, and the trehalose in the modified nano-calcium carbonate can promote the uniform dispersion of the fumed silica to a certain extent, thereby obtaining a more excellent silicone sealant.
[0031] In summary, the present invention has the following beneficial effects:
[0032] 1. The organic silicone sealant of the present invention is compounded with hydroxyl-terminated polydimethylsiloxane and specific modified nano-calcium carbonate, polylactic acid and other additives in strict accordance with the set amount. The modified nano-calcium carbonate does not contain metal ions such as Na+, and the modified nano-calcium carbonate and polylactic acid can synergistically reinforce the organic silicone sealant under low temperature environment, and then cooperate with a set amount of dimethyl silicone oil for lubrication, thereby effectively improving the low-temperature tear resistance of the organic silicone sealant.
[0033] 2. The present invention strictly controls the amount of trehalose and polyvinyl alcohol used, thereby obtaining modified nano calcium carbonate with little effect on the waterproofness of the sealant and excellent cross-linking effect.
[0034] 3. The hydroxyl-terminated polydimethylsiloxane in the silicone sealant of the present invention is compounded with a specific ratio of low-viscosity type and high-viscosity type, which helps to further improve the cross-linking effect with modified nano-calcium carbonate and polylactic acid, so that the sealant obtained has higher low-temperature tear resistance.
[0035] 4. By adding a set amount of fumed silica to the organic silicone sealant of the present invention, it can work synergistically with the modified nano-calcium carbonate, not only further increasing the crosslinking density of the sealant to improve the low-temperature tear resistance, but also improving the anti-ultraviolet oxidation performance of the sealant.
[0036] 5. When preparing the silicone sealant of the present invention, the modified nano-calcium carbonate is mixed with the hydroxyl-terminated polydimethylsiloxane twice, which is more conducive to the step-by-step cross-linking of the hydroxyl-terminated polydimethylsiloxane, thereby improving the cross-linking effect of the sealant and further improving the low-temperature tear resistance of the sealant. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0038] Preparation examples of raw materials and / or intermediates
[0039] The hydroxyl-terminated polydimethylsiloxane, raw materials for preparing modified nano calcium carbonate, dimethyl silicone oil, crosslinking agent, coupling agent, catalyst and fumed silica are all commercially available products.
[0040] Among them, the hydroxyl-terminated polydimethylsiloxane is selected from α, ω-dihydroxy polydimethylsiloxane, and further preferably a mixture of low-viscosity α, ω-dihydroxy polydimethylsiloxane (viscosity of 10000-50000 mPa·s at 25°C) and high-viscosity α, ω-dihydroxy polydimethylsiloxane (viscosity of 500000-1000000 mPa·s at 25°C) in a weight ratio of 100:(20-30).
[0041] The polylactic acid uses 800-mesh polylactic acid powder, with an effective component content of 99% and a molecular weight of 100,000.
[0042] The dimethyl silicone oil can be 201 methyl silicone oil, and the viscosity is 100-500 mPa·s at 25°C. The dimethyl silicone oil can give the low-temperature tear-resistant silicone sealant better low-temperature flexibility, that is, the low-temperature tear-resistant silicone sealant is not easy to crack at low temperatures.
[0043] The crosslinking agent can be selected from one or more combinations of methyl tributylacetonato silane, phenyl tributylacetonato silane, vinyl tributylacetonato silane, methyl triacetone oxime silane, and vinyl triacetone oxime silane, which helps to maintain the flexibility and tear resistance of the low-temperature tear-resistant silicone sealant system at low temperatures.
[0044] The coupling agent may be at least one of KH-550 and KH-560, which can further modify the combination of nano calcium carbonate and polylactic acid and hydroxyl-terminated polydimethylsiloxane to enhance the overall performance of the silicone sealant.
[0045] The catalyst can be selected from at least one of dioctyltin dilaurate, stannous octoate and tin dibutyl acetylacetonate.
[0046] The fumed silica is specifically purchased from Wanhua Tianhe's TH-8150 fumed hydrophobic silica, which has a better dispersion effect.
[0047] Trehalose is selected from products with CAS number 99-20-7, and the content of effective substances is ≥ 98%.
[0048] Chitosan is selected from products with CAS number 9012-76-4, and the content of effective substances is ≥ 99%.
[0049] The polyvinyl alcohol is PVA 17-92 powder, and the dissolution temperature is 75-80°C.
[0050] The present invention is further described in detail below with reference to Examples and Comparative Examples.
[0051] Example
[0052] Example 1
[0053] A method for preparing a low-temperature tear-resistant silicone sealant comprises the following steps:
[0054] (1) Preparation of modified nano calcium carbonate (taking 1 kg of saturated Ca(OH)2 slurry as an example)
[0055] Weigh 1kg of saturated Ca(OH)2 slurry and put it into an emulsifying disperser, add 60g of trehalose to the saturated Ca(OH)2 slurry and stir evenly, then introduce CO2 gas and the saturated Ca(OH)2 slurry for mixing and carbonization, when the pH of the system is 9 (allowed to fluctuate within the range of ±0.2), heat to 85°C and add 40g of polyvinyl alcohol for uniform dispersion, continue to introduce CO2 gas while cooling for mixing and emulsification, when the temperature of the system drops to room temperature and the pH is 7.5 (allowed to fluctuate within the range of ±0.2), stop introducing CO2 gas to obtain modified CaCO3 slurry; filter the modified CaCO3 slurry, dry and pulverize to obtain modified nano calcium carbonate;
[0056] (2) Preparation of base material
[0057] Weigh 720g of modified nano-calcium carbonate and divide it into two parts, each part is 360g, take one part of the modified nano-calcium carbonate, first blend it with 1000g of hydroxyl-terminated polydimethylsiloxane (mixed by α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000mPa·s at 25°C and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 600000mPa·s at 25°C in a weight ratio of 4:1) and 180g of polylactic acid at a temperature of 165°C and a vacuum degree of -0.08MPa for 30min, then take another part of the modified nano-calcium carbonate and add it, continue blending for 70min, and obtain a base material after cooling;
[0058] (3) Preparation of sealant
[0059] The base material, 120 g of dimethyl silicone oil, 100 g of methyl tributylidene oxime silane, 40 g of a coupling agent (mixed by weight ratio of 1:1 between KH-550 and KH-560), and 15 g of dioctyltin dilaurate were put into a planetary mixer for mixing, and the mixture was stirred for 100 min at a vacuum degree of -0.09 MPa and a stirring speed of 500 rpm to obtain a low-temperature tear-resistant silicone sealant.
[0060] Embodiment 2-6
[0061] Examples 2-6 are based on the method of Example 1, and the amounts of modified nano-calcium carbonate, dimethyl silicone oil, crosslinking agent, coupling agent and catalyst in the silicone sealant components and the process parameters of the silicone sealant are adjusted. The specific adjustments are shown in Table 1 below.
[0062] Table 1 Component dosage and process parameters of the silicone sealant of Examples 1-6
[0063]
[0064]
[0065] Examples 7-12
[0066] Examples 7-12 are based on the method of Example 1, and the amount of the raw material of modified nano-calcium carbonate in the silicone sealant component is adjusted. The specific adjustment details are shown in Table 2 below.
[0067] Table 2 Raw material dosage of modified nano calcium carbonate in Examples 1, 7-12 (g)
[0068]
[0069] Examples 13-17
[0070] Examples 13-17 are based on the method of Example 1, and the hydroxyl-terminated polydimethylsiloxane in the silicone sealant component is adjusted.
[0071] The hydroxy-terminated polydimethylsiloxane of Example 13 is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 20000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 600000 mPa·s at 25° C. in a weight ratio of 3:1;
[0072] The hydroxyl-terminated polydimethylsiloxane of Example 14 is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 20000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 600000 mPa·s at 25° C. in a weight ratio of 78:22;
[0073] The hydroxy-terminated polydimethylsiloxane of Example 15 is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 30000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 700000 mPa·s at 25° C. in a weight ratio of 4:1;
[0074] The hydroxy-terminated polydimethylsiloxane of Example 16 is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 40000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 600000 mPa·s at 25° C. in a weight ratio of 4:1;
[0075] The hydroxy-terminated polydimethylsiloxane of Example 17 is prepared by mixing α,ω-dihydroxy polydimethylsiloxane having a viscosity of 10000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane having a viscosity of 1000000 mPa·s at 25° C. in a weight ratio of 4:1.
[0076] Examples 18-20
[0077] Examples 18-20 are based on the method of Example 1, and the components of the silicone sealant are further added with fumed silica. The preparation method of the above examples includes the following steps:
[0078] (1) Preparation of modified nano calcium carbonate: the same preparation method as in Example 1;
[0079] (2) Preparation of base material
[0080] Weigh 720g of modified nano-calcium carbonate and divide it into two portions, each portion is 360g, and one portion of the modified nano-calcium carbonate is firstly mixed with 1000g of hydroxyl-terminated polydimethylsiloxane (mixed by α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000mPa·s at 25°C and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 600000mPa·s at 25°C in a weight ratio of 4:1) and 180g of polylactic acid at a temperature of 165°C and a vacuum degree of -0.08MPa for 30min, and then the other portion of the modified nano-calcium carbonate and a set amount of fumed silica are added and the mixture is continuously mixed for 70min, and a base material is obtained after cooling;
[0081] Among them, the amount of fumed silica added in Example 18 is 100g (i.e., the weight ratio of fumed silica to modified nano-calcium carbonate is 1:7.2); the amount of fumed silica added in Example 19 is 120g (i.e., the weight ratio of fumed silica to modified nano-calcium carbonate is 1:6); the amount of fumed silica added in Example 20 is 150g (i.e., the weight ratio of fumed silica to modified nano-calcium carbonate is 1:4.8);
[0082] (3) Preparation of sealant: The preparation method is the same as that in Example 1, and a low-temperature tear-resistant silicone sealant is obtained.
[0083] Embodiment 21
[0084] A method for preparing a low-temperature tear-resistant silicone sealant comprises the following steps:
[0085] (1) Preparation of modified nano calcium carbonate: the same preparation method as in Example 1;
[0086] (2) Preparation of base material
[0087] 720 g of modified nano-calcium carbonate, 1000 g of hydroxyl-terminated polydimethylsiloxane (mixed by α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 600000 mPa·s at 25° C. in a weight ratio of 4:1) and 180 g of polylactic acid were blended at a temperature of 165° C. and a vacuum degree of -0.08 MPa for 100 min, and a base material was obtained after cooling;
[0088] (3) Preparation of sealant: The preparation method is the same as that in Example 1, and a low-temperature tear-resistant silicone sealant is obtained.
[0089] Embodiment 22
[0090] A method for preparing a low-temperature tear-resistant silicone sealant comprises the following steps:
[0091] (1) Preparation of modified nano calcium carbonate: the same preparation method as in Example 1;
[0092] (2) Preparation of base material
[0093] 720 g of modified nano-calcium carbonate, 180 g of polylactic acid, 120 g of fumed silica and 1000 g of hydroxyl-terminated polydimethylsiloxane (mixed by α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000 mPa·s at 25° C. and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 600000 mPa·s at 25° C. in a weight ratio of 4:1) were weighed and blended for 100 min at a temperature of 165° C. and a vacuum degree of -0.08 MPa, and a base material was obtained after cooling;
[0094] (3) Preparation of sealant: The preparation method is the same as that in Example 1, and a low-temperature tear-resistant silicone sealant is obtained.
[0095] Comparative Example
[0096] Comparative Example 1
[0097] In this comparative example, based on the method of Example 1, the modified nano-calcium carbonate is replaced by commercially available active nano-calcium carbonate with CAS No. 471-34-1.
[0098] Comparative Example 2
[0099] In this comparative example, based on the method of Example 1, the modified nano-calcium carbonate is replaced with other existing modified nano-calcium carbonate, and the specific modification steps include the following steps:
[0100] The n-butyl titanate and the silane coupling agent KH-960 in a weight ratio of 1:1 are uniformly mixed to obtain a composite modifier, and the composite modifier is added to commercially available active nano-calcium carbonate with a CAS number of 471-34-1 for mixing. The amount of the composite modifier added is 2% of the total weight of the modified nano-calcium carbonate. The temperature is raised to 150° C. and reacted for 6 hours for surface coating treatment to obtain the modified nano-calcium carbonate.
[0101] Comparative Example 3
[0102] This comparative example is based on the method of Example 1, but without adding polylactic acid.
[0103] Comparative Example 4
[0104] In this comparative example, based on the method of Example 1, an equal amount of chitosan was used to replace trehalose in the preparation of modified nano-calcium carbonate.
[0105] Performance testing
[0106] The silicone sealants prepared in Examples 1-22 and Comparative Examples 1-3 of the present invention were used as test pieces and placed in a UV test box for 300 hours of immersion and illumination. The power of the UV lamp was 300W, the distance between the lamp and the test piece was 250mm, and the UV radiation intensity was 3000μW / cm 2 , the water temperature is 40±5℃, after the immersion and illumination, the surface moisture is taken out and wiped dry, and then the following performance test is carried out, and the test results are shown in Table 3 below. Among them, the above-mentioned "immersion and illumination" is to increase the test difficulty of the sample, which is based on further verifying whether the modified nano-calcium carbonate of the present invention will affect the performance of the sealant after being modified by trehalose.
[0107] (1) Tear strength test: Tested according to ASTM D624, using type C specimens.
[0108] (2) Low temperature flexibility test: Tested according to Part VII of GB / T13477.
[0109] Table 3 Test results of silicone sealants of Examples 1-22 and Comparative Examples 1-3
[0110]
[0111] Referring to Table 3, compared with Comparative Examples 1-4, the silicone sealant prepared in Examples 1-22 of the present invention still has excellent tear strength and low-temperature flexibility at -50°C and -70°C after being immersed in water and exposed to ultraviolet light, and can still maintain a relatively high tear strength and relatively excellent low-temperature flexibility at -90°C, which shows that the silicone sealant of the present invention has excellent low-temperature tear resistance, water resistance and ultraviolet aging resistance. In addition, the modified nano-calcium carbonate of the present invention adopts trehalose modification, and has better tear strength and low-temperature flexibility under low temperature conditions than other modified nano-calcium carbonates (including modified nano-calcium carbonate prepared by replacing trehalose with an equal amount of chitosan).
[0112] By comparing the test results of Examples 1-6, it can be found that when the modified nano-calcium carbonate, polylactic acid and dimethyl silicone oil are configured in a weight ratio of 72:18:12, the obtained silicone sealant has a more excellent low-temperature tear resistance, so it is further preferred. In addition, when preparing the silicone sealant of the present invention, the blending temperature of hydroxyl-terminated polydimethylsiloxane, modified nano-calcium carbonate and polylactic acid is 160-170°C to obtain a silicone sealant with better performance. This may be because the polylactic acid particles at this temperature are in a softened state, which can better participate in the cross-linking reaction of the modified nano-calcium carbonate and the hydroxyl-terminated polydimethylsiloxane, thereby obtaining a tighter network structure.
[0113] By comparing the test results of Example 1 with those of Examples 7-12, it can be obtained that in the organic silicone sealant of the present invention, when preparing modified nano-calcium carbonate, the addition amount of trehalose and polyvinyl alcohol will affect the effect of modified nano-calcium carbonate on the organic silicone sealant. Among them, when the addition amount of trehalose is 5-8% of the weight of the saturated Ca(OH)2 slurry and the addition amount of polyvinyl alcohol is 3-6% of the weight of the saturated Ca(OH)2 slurry, the organic silicone sealant prepared by the modified nano-calcium carbonate obtained has better tear strength and low-temperature flexibility at -50°C and -70°C; in addition, when the weight ratio of trehalose to polyvinyl alcohol is 3:2, the organic silicone sealant can still maintain excellent tear strength and low-temperature flexibility at -90°C, so it is further preferred.
[0114] Combining the test results of Example 1 with Examples 13-17, it can be obtained that in the silicone sealant of the present invention, when the hydroxyl-terminated polydimethylsiloxane is mixed with α,ω-dihydroxypolydimethylsiloxane with a viscosity of 10000-50000 mPa·s at 25°C and α,ω-dihydroxypolydimethylsiloxane with a viscosity of 500000-1000000 mPa·s at 25°C in a weight ratio of 75-80:25-20, it has excellent tear strength and low-temperature flexibility at -50°C, -70°C and -90°C.
[0115] Among them, by comparing the test results of Example 1 with those of Examples 13-17, it can be seen that the specific type of hydroxyl-terminated polydimethylsiloxane in the present invention will also affect the performance of the silicone sealant. When the low-viscosity hydroxyl-terminated polydimethylsiloxane (referred to as the low-viscosity type) and the high-viscosity hydroxyl-terminated polydimethylsiloxane (referred to as the high-viscosity type) are used in combination with each other, the greater the amount of the low-viscosity type, the higher the tear strength of the silicone sealant obtained at a relatively high temperature, and the better the tear strength retention effect at low temperatures; in addition, the higher the viscosity of the low-viscosity type and the high-viscosity type, the worse the tear strength retention effect of the silicone sealant obtained at low temperatures. The present invention further prefers a hydroxyl-terminated polydimethylsiloxane formed by mixing α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000mPa·s at 25°C and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 600000mPa·s at 25°C in a weight ratio of 4:1.
[0116] By comparing the test results of Example 1 with those of Examples 18-20, it can be concluded that the organic silicon sealant of the present invention is additionally added with a set amount of fumed silica, which can cooperate with the modified nano-calcium carbonate to further increase the crosslinking density of the sealant, and the obtained sealant has a more excellent low-temperature tear resistance. Among them, when the weight ratio of fumed silica to modified nano-calcium carbonate is 1:6 (Example 19), the effect of the obtained organic silicon sealant is significantly better than the others (Examples 18 and 20), so it is further preferred.
[0117] By comparing the test results of Example 1 with those of Example 21, it can be concluded that, when preparing the silicone sealant, the modified nano-calcium carbonate is mixed with the hydroxyl-terminated polydimethylsiloxane twice in the present invention. Compared with adding it all at once, the dispersion efficiency of the mixed mixture in batches in the present invention is higher, and it is more conducive to the step-by-step cross-linking of the hydroxyl-terminated polydimethylsiloxane, thereby improving the cross-linking effect of the sealant, and further improving the low-temperature tear resistance of the sealant after immersion in water and illumination.
[0118] By comparing the test results of Example 19 with those of Example 22, it can be obtained that, in addition to adding fumed silica, the present invention adds fumed silica together with the modified nano-calcium carbonate for the second time. At this time, the hydroxyl-terminated polydimethylsiloxane has completed the initial cross-linking, and the trehalose in the modified nano-calcium carbonate can promote the uniform dispersion of fumed silica to a certain extent, thereby obtaining a more excellent silicone sealant.
[0119] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A low temperature tear resistant silicone sealant, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of hydroxyl-terminated polydimethylsiloxane, 60-80 parts of modified nano calcium carbonate, 15-20 parts of polylactic acid, 10-15 parts of dimethyl silicone oil, 8-12 parts of a crosslinking agent, 3-5 parts of a coupling agent, and 1-2 parts of a catalyst; The preparation method of the modified nano calcium carbonate comprises the following steps: adding trehalose to a saturated Ca(OH)2 slurry and stirring evenly, then introducing CO2 gas and the saturated Ca(OH)2 slurry for mixing and carbonization, heating the system to 80-85°C and adding polyvinyl alcohol when the pH value of the system is 9±0.2, continuing to introduce CO2 gas while cooling the system for mixing after the system is evenly dispersed, and stopping introducing CO2 gas when the pH value of the system is 7.5±0.2 to obtain a modified CaCO3 slurry; subjecting the modified CaCO3 slurry to pressure filtration, drying and pulverizing to obtain the modified nano calcium carbonate; The amount of trehalose added is 5-8% of the weight of the saturated Ca(OH)2 slurry, and the amount of polyvinyl alcohol added is 3-6% of the weight of the saturated Ca(OH)2 slurry; The hydroxyl-terminated polydimethylsiloxane is prepared by mixing α,ω-dihydroxy polydimethylsiloxane with a viscosity of 10000-50000 mPa·s at 25°C and α,ω-dihydroxy polydimethylsiloxane with a viscosity of 500000-1000000 mPa·s at 25°C in a weight ratio of 75-80:25-20.
2. The low temperature tear resistant silicone sealant according to claim 1, characterized in that: The weight ratio of the trehalose to the polyvinyl alcohol is 3:
2.
3. The low temperature tear resistant silicone sealant according to claim 1, characterized in that: The weight ratio of the modified nano-calcium carbonate, the polylactic acid and the dimethyl silicone oil is 72:18:
12.
4. The low temperature tear resistant silicone sealant according to claim 1, characterized in that: Also included is 10-15 parts of fumed silica.
5. The low temperature tear resistant silicone sealant according to claim 4, characterized in that: The weight ratio of the fumed silica to the modified nano calcium carbonate is 1:
6.
6. The method for preparing the low-temperature tear-resistant silicone sealant according to any one of claims 1 to 3, characterized in that: The following steps are involved: Divide a set amount of modified nano-calcium carbonate into two parts, take one part of the modified nano-calcium carbonate and first blend it with a set amount of hydroxyl-terminated polydimethylsiloxane and polylactic acid at a temperature of 160-170° C. and a vacuum degree of -0.06 to -0.09 MPa for 30 minutes, then take another part of the modified nano-calcium carbonate and add it and continue blending for 60-80 minutes, and obtain a base material after cooling; The base material is mixed with a set amount of dimethyl silicone oil, a crosslinking agent, a coupling agent, and a catalyst, and stirred for reaction for 60-120 minutes under a vacuum degree of -0.08 to -0.09 MPa to obtain the low-temperature tear-resistant silicone sealant.
7. The method for preparing the low-temperature tear-resistant silicone sealant according to claim 6, characterized in that: The following steps are involved: Divide a set amount of modified nano-calcium carbonate into two parts, take one part of the modified nano-calcium carbonate and first blend it with a set amount of hydroxyl-terminated polydimethylsiloxane and polylactic acid at a temperature of 160-170° C. and a vacuum degree of -0.06 to -0.09 MPa for 30 minutes, then take another part of the modified nano-calcium carbonate and fumed silica and add them and continue blending for 60-80 minutes, and obtain a base material after cooling; The base material is mixed with a set amount of dimethyl silicone oil, a crosslinking agent, a coupling agent, and a catalyst, and stirred for reaction for 60-120 minutes under a vacuum degree of -0.08 to -0.09 MPa to obtain the low-temperature tear-resistant silicone sealant.
Citation Information
Patent Citations
Polylactic acid composite modified material and preparation method thereof
CN107936506A
High-strength sealant for electronic product and preparation method of high-strength sealant
CN109337589A